COMPETITIVENESS AND DEVELOPMENT PHARMACEUTICAL INDUSTRY OF KAZAKHSTAN - M. U. Spanov; P. Zh. Orynbet (Экономика: стратегия и практика, 2019)
The purpose of this study to determine the degree of influence of various economic indicators of the competitiveness of the pharmaceutical industry of Kazakhstan and define the growth factors in the conditions of the Common Market of the drug. The work revealed the factors affecting the production of the main pharmaceutical products of the Republic of Kazakhstan, from the very formation of the country’s independence. That is, the indicators for 1990-2018 are analyzed. The study was conducted using the methods of economic and mathematical modeling, statistical and comparative analysis. A detailed analysis of the development of the pharmaceutical industry was carried out, as well as the degree of influence of factors such as: GDP of the Republic of Kazakhstan, per capita GDP, population, wage, average monthly nominal wage of one employee, investment in fixed assets, investment in fixed assets, farm, was estimated. industries, commodity turnover in foreign currency (export), commodity circulation in foreign currency (import), industry in general, manufacturing industry in general, indices of industrial production pharm. industry and the number of operating enterprises and pharmaceutical production. products. The results of the study allow us to conclude which of these factors significantly strengthens the competitive position of the domestic pharmaceutical industry. These results are very important in making decisions and developing the pharmaceutical industry of Kazakhstan in the context of creating a Common Market of the drug within the EAEU.